Asymmetric synthesis of tetrahydroquinolin-3-ols via CoCl2-catalyzed reductive cyclization of nitro cyclic sulfites with NaBH4 - Jagdale, Arun R.; Reddy, R. Santhosh; Sudalai, Arumugam (Organic Letters, 2009)
A new method for the construction of chiral 3-substituted tetrahydroquinoline derivatives based on asymmetric dihydroxylation and CoCl2-catalyzed reductive, cyclization of nitro cyclic sulfites with NaBH4 has been described with high optical purities. This method has been successfully applied in the formal synthesis of PNU 95666E and anachelin H chromophore.

Asymmetric synthesis of (+)-stagonolide C and (-)-aspinolide A via organocatalysis - Shelke, Anil M.; Rawat, Varun; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2012)
A new enantioselective synthesis of two important fungal metabolites, (+)-stagonolide C and (-)-aspinolide A, has been described from readily available raw materials. Praline catalyzed asymmetric alpha-aminooxylation and Jorgensen's epoxidation of aldehydes are the key reactions employed in the introduction of chirality. The formation of the 10-membered lactone core structure was finally accomplished via Steglich esterification and ring closing metathesis reactions. (C) 2012 Elsevier Ltd. All rights reserved.